What Drives Heterogeneity in Foreign Exchange Rate Expectations: Deep Insights from a New Survey - Christian Dreger; Georg Stadtmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Foreign exchange rate expectations play a central role in virtually all monetary models for the open economy. Therefore, it is extremely important to gain empirical insights into the expectations formation process. In this paper, we use a unique disaggregated data set to model the expectations of the Yen/USD exchange rate of about 50 leading foreign exchange rate professionals. The survey includes not only forecasts of the exchange rate, but also for macroeconomic fundamentals, like GDP growth, inflation, and interest rates. Different expectations of fundamentals might lead to different views of exchange rate dynamics. Using panel models, we are able to confirm the heterogeneity of exchange rate expectations often detected by former authors. More important, we provide strong evidence regarding the likely source of heterogeneity. In line with forward looking models for the exchange rate, expected fundamentals have a substantial impact on exchange rate expectations, thereby challenging the backward looking evidence of previous studies. However, the heterogeneity in the expectations of macroeconomic fundamentals is not sufficient to explain the heterogeneity in exchange rate expectations.
Keywords: F37; F31; C23; 330; Exchange rate expectations; heterogeneity of expectations; expected fundamentals